TCF7L2 and therapeutic response to sulfonylureas in patients with type 2 diabetes - Stumvoll Michael; Körner Antje; Hahn Michael; Holstein Andreas; Kovacs Peter (BMC, 2011)
Abstract Background Variants in the TCF7L2 have been shown to be associated with an increased risk for type 2 diabetes (T2D). Since the association with diabetes could be explained by effects on insulin secretion, we investigated whether patients with diabetes risk alleles at rs7903146 might have an altered hypoglycaemic response to sulfonylureas (SUs). Methods We recruited 189 patients with T2D being treated with SUs and determined the rs7903146 diabetes risk genotype. We used a logistic regression with secondary SU failure defined as an A1C ≥7.0% after 6 months of SU treatment. Results In univariate regression analyses, TCF7L2 genotype was the only predictor of SU treatment failure. The rs7903146 T allele was significantly more frequent in the group of patients who failed to respond to SU (36%) than in the control group (26%) [P = 0.046; odds ratio (OR): 1.57 (1.01-2.45) in an additive mode of inheritance]. Conclusions Our data suggest that patients with diabetes risk alleles in TCF7L2 have an altered hypoglycaemic response to SUs resulting in earlier secondary failure.